2006
DOI: 10.1176/ps.2006.57.8.1179
|View full text |Cite
|
Sign up to set email alerts
|

The Treatment Relationship in Peer-Based and Regular Case Management for Clients With Severe Mental Illness

Abstract: Early in treatment, peer providers may possess distinctive skills in communicating positive regard, understanding, and acceptance to clients and a facility for increasing treatment participation among the most disengaged, leading to greater motivation for further treatment and use of peer-based community services. Findings strongly suggest that peer providers serve a valued role in quickly forging therapeutic connections with persons typically considered to be among the most alienated from the health care serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 124 publications
(40 citation statements)
references
References 21 publications
2
37
0
1
Order By: Relevance
“…One study (Solomon and Draine 1995b) reported lower satisfaction with services in the consumer-led intervention. Sells and colleagues (Sells et al 2006) found that clients of the consumer-led intervention had greater satisfaction with services earlier in the intervention process, with traditional services catching up after 1 year, which might provide one possible explanation for the heterogeneity in results for this outcome. Another explanation is that studies often reported very high levels of satisfaction with services for both consumer and nonconsumer groups, although some studies reported a small but statistical significant difference between the groups.…”
Section: Satisfaction With Servicesmentioning
confidence: 99%
“…One study (Solomon and Draine 1995b) reported lower satisfaction with services in the consumer-led intervention. Sells and colleagues (Sells et al 2006) found that clients of the consumer-led intervention had greater satisfaction with services earlier in the intervention process, with traditional services catching up after 1 year, which might provide one possible explanation for the heterogeneity in results for this outcome. Another explanation is that studies often reported very high levels of satisfaction with services for both consumer and nonconsumer groups, although some studies reported a small but statistical significant difference between the groups.…”
Section: Satisfaction With Servicesmentioning
confidence: 99%
“…For example, Villano et al (2005) found that clinicians' beliefs about dually-diagnosed clients' capacity for recovery was associated with less frequent referrals to self-help groups. Such changes in referral practices may limit the degree to which individuals are exposed to peer-based or peer-run supports-considered key elements of a recovery-oriented system of care (Davidson et al 2009) and an effective practice at engaging difficult to engage clients (Sells et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, bilingual capacity is important for outreach to and engagement of monolingual Spanish speakers (or speakers of other languages, if relevant). Employing peer outreach workers with a history of homelessness may also be helpful, as research has shown that peer staff working on intensive community-based teams have a unique capacity to engage persons who are most ''disengaged'' from treatment into treatment and self-help groups Sells et al 2006Sells et al , 2008.…”
Section: Demographicsmentioning
confidence: 99%